Myeloid Vamp3 deletion attenuates CFA-induced inflammation and pain in mice via ameliorating macrophage infiltration and inflammatory cytokine production - Dai, Xiaolong; Li, Lianlian; Yan, Xinrong; Fan, Qianqian; Wang, Ruizhen; Zhang, Wenhao; Chen, Weiwei; Liu, Yang; Meng, Jianghui; Wang, Jiafu (Frontiers in Immunology, 2023)
Persistent inflammation and associated pain significantly impact individuals' quality of life, posing substantial healthcare challenges. Proinflammatory cytokines, released by activated macrophages, play crucial roles in the development of chronic inflammatory conditions such as rheumatoid arthritis. To identify and evaluate potential therapeutic interventions targeting this process for mitigating inflammation and pain, we created a myeloid cell-specific knockout of Vamp3 (vesicleassociated membrane protein 3) mice (Vamp3 Δmyel ) by crossing LysM-Cre mice with newly engineered Vamp3 flox/flox mice. Bone marrow-derived macrophages and peritoneal resident macrophages from Vamp3 Δmyel mice exhibited a significant reduction in TNF-α and IL-6 release compared to control mice. Moreover, Vamp3 deficiency led to decreased paw edema and ankle joint swelling induced by complete Freund's adjuvant (CFA). Furthermore, Vamp3 depletion also mitigated CFA-induced mechanical allodynia and thermal hyperalgesia. Mechanistically, Vamp3 loss ameliorated the infiltration of macrophages in peripheral sites of hind paw and resulted in reduced levels of TNF-α and IL-6 in the CFA-injected paw and serum. RT-qPCR analysis demonstrated downregulation of various inflammation associated genes, including TNF-α, IL-6, IL-1β, CXCL11, TIMP-1, COX-2, CD68 and CD54 in the injected paw at the test day 14 following CFA administration. These findings highlight the novel role of Vamp3 in regulating inflammatory responses and suggest it as a potential therapeutic target for the development of novel Vampinactivating therapeutics, with potential applications in the management of inflammatory diseases.